Nomadic Sisters: Migrant Identity in Joanna Bator’s Cloudalia and Sandra Cisneros’ Caramelo - Gondor-Wiercioch, Agnieszka (Porównania, 2023)
The article provides a comparative analysis of Joanna Bator’s Cloudalia and Sandra Cisneros’ Caramelo with regard to similar identity construction of the main female characters. Both authors concentrate on young women (Dominika Chmura in Cloudalia and Celaya Reyes in Caramelo) who set out for a journey of feminist self-discovery, crossing the boundaries of geography, history and culture. The author of the article argues that, despite the obvious differences between Poland and Mexico, the protagonists rebel against the same legacy of the Catholic patriarchal culture, reinforced by national visions of history and literary canon in the respective countries, and they gradually manage to rework historical trauma by reconstructing the doppelganger figure and creating new transcultural feminist paradigms. The arguments are reinforced not only by references to autobiographical motives in Bator’s and Cisneros’ fiction and diaries, but also by transnational identity studies of Zygmunt Bauman and Amaryll Chanady.